Correlates of Health Behaviors in Patients With Coronary Artery Disease - Younhee Kang, RN, MSN-ANP, PhD; In-Suk Yang, RN, MSN; Narae Kim, RN, BSN (Elsevier, 2010)
To investigate the effect of cardiac knowledge and cardiac self-efficacy on health behaviors after controlling for influences from associating factors of health behaviors in patients with coronary artery diseases (CADs). Methods: A descriptive correlational and cross-sectional design was used. Subjects with CADs were recruited from outpatient clinics of three academic medical centers. The cardiac knowledge, cardiac self-efficacy, and health behaviors were measured by Coronary Heart Disease Awareness and Knowledge Questionnaire, Cardiac Self-Efficacy Scale, and Health-Promoting Lifestyle Profile II respectively. The data collected were statistically analyzed by descriptive statistics, t test, Kruskal-Wallis test, analysis of variance, Pearson's correlation analysis, and the hierarchical multiple regression analysis. Results: A total of 157 subjects were recruited for this study. The mean age of subjects was 59.38 ± 10.04 years, and three-fourths (75.2%) were male. Subjects showed relatively low cardiac knowledge, moderately high cardiac self-efficacy, and moderate level of health behaviors. The overall model significantly explained 48% of variance in health behaviors (F = 14.52, p < .001). Among predictors, age, education, smoking status, experience of receiving patient education, and cardiac self-efficacy significantly affected health behaviors, and cardiac self-efficacy had the greatest effect on health behaviors (β= .39). However, cardiac knowledge had no statistically significant influence on health behaviors after controlling for the other factors. Conclusion: The findings suggested that cardiac self-efficacy was shown to be the most influencing factor on health behaviors but cardiac knowledge had no influence on health behaviors. The nursing interventions tailored on the patient characteristics should be developed in order to improve the health behaviors of patients with CADs.